2005
DOI: 10.1021/es048136a
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Organic Contaminant Uptake, Storage, and Metabolism within Plant Roots

Abstract: Vegetation plays a key role in the environmental cycling and fate of many organic chemicals. A compound's location on or within leaves will affect its persistence and significance; retention in surface compartments (i.e., the epicuticular wax and cuticle) renders the compound more susceptible to photodegradation and volatilization, while penetration into the epidermal cell walls or cytoplasm will enhance susceptibility to metabolism. Here, for the first time, methodologies which combine plant and PAH autofluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
169
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(180 citation statements)
references
References 20 publications
11
169
0
Order By: Relevance
“…A previous study that involved the live imaging of maize and wheat roots for uptake of anthracene and phenanthrene, kinds of polycyclic aromatic hydrocarbons, demonstrated that such hydrophobic compounds localized in the cortex of the exposed living roots. 26) This study is partially consistent with our results for perylene uptake in the respect of its passage through the epidermis, whereas the previous researchers could not detect the radial movement of their compounds to inner tissues beyond the cortex. In addition to differences in the experimental conditions, the thickness of their root samples might make it difficult to detect fluorescence in such deep areas, thus causing the different findings between our study and theirs.…”
Section: Uptake Of Hydrophobic Perylenesupporting
confidence: 92%
“…A previous study that involved the live imaging of maize and wheat roots for uptake of anthracene and phenanthrene, kinds of polycyclic aromatic hydrocarbons, demonstrated that such hydrophobic compounds localized in the cortex of the exposed living roots. 26) This study is partially consistent with our results for perylene uptake in the respect of its passage through the epidermis, whereas the previous researchers could not detect the radial movement of their compounds to inner tissues beyond the cortex. In addition to differences in the experimental conditions, the thickness of their root samples might make it difficult to detect fluorescence in such deep areas, thus causing the different findings between our study and theirs.…”
Section: Uptake Of Hydrophobic Perylenesupporting
confidence: 92%
“…Two-photon excitation microscopy coupled with autofluorescence (TPEM-AF) has provided a powerful technique that enables the visualization and tracking of how organic pollutants are taken up into plants and how they behave once within the living plant tissues (13). Wild and his coworkers have pioneered the use of this technique to track the uptake and movement of PAH inside living plant leaves (14) and roots (15). They observed that for root uptake the PAHs anthracene and phenanthrene initially bound to the epidermis along the zone of elongation, passing through the epidermal cells to reach the cortex within the root hair and branching zones of the root.…”
Section: Introductionmentioning
confidence: 99%
“…The need for better understanding the mechanism and influential factors on plant uptake has prompted a series of studies on the plant-uptake process in recent times (Riederer, 1990;Paterson et al, 1994;Trapp, 1995;Trapp and Mathies, 1995;Burken and Schnoor, 1997;Weiss, 2000;Li et al, 2002Li et al, , 2005Wild et al, 2005). Analyses of the concentrations of nonionic contaminants in plants in relation to the external levels in water (or soil solution) from extensive sources have revealed that these contaminants enter plants largely via a passive (i.e., partition) process (Briggs et al, 1982;Chiou et al, 2001;Trapp, 2004;Su and Zhu, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the concentrations of nonionic contaminants in plants in relation to the external levels in water (or soil solution) from extensive sources have revealed that these contaminants enter plants largely via a passive (i.e., partition) process (Briggs et al, 1982;Chiou et al, 2001;Trapp, 2004;Su and Zhu, 2006). The magnitude and efficiency of plant uptake depends in principle on contaminant level and properties, plant species/composition, exposure time, and other variables (Briggs et al, 1982;Chiou et al, 2001;Trapp, 2004;Wild et al, 2005). Previously, we have studied the uptake of atrazine by rice seedlings from nutrient solution with and without coexisting organic and metal-ion species (Su et al, 2005;Su and Zhu, 2006).…”
Section: Introductionmentioning
confidence: 99%